Fight of the century : Alice Paul battles Woodrow Wilson for the vote - Rosenstock, Barb (Calkins Creek, an imprint of Boyds Mills & Kane, 2020)
"This fight determines whether the women of the United States can vote, folks. The winner changes the country forever."--Back cover.